Translation and validation of a Bahasa Malaysia (Malay) version of the Functionality Appreciation Scale. (September 2019) - Swami, Viren; Todd, Jennifer; Aspell, Jane E.; Mohd. Khatib, Nor Azzatunnisak; Toh, Evelyn Kheng Lin; Zahari, Hanoor Syahirah; Barron, David
Highlights: Scores on Malay Functionality Appreciation Scale (FAS) are 1-dimensional. Malay FAS scores are internally reliable and have good construct validity. Malay FAS scores are sex invariant and not significantly different between women and men. Abstract: The Functionality Appreciation Scale (FAS; Alleva et al., 2017) is a 7-item measure of an individual's appreciation of their body for what it can do and is capable of doing. To date, its psychometric properties have not been examined beyond the parent study and outside English-speaking samples. To rectify this, we examined the psychometric properties of a Bahasa Malaysia (Malay) translation of the FAS. An online sample of 815 Malaysia citizens completed a Malay translation of the FAS, along with validated measures of body appreciation, weight discrepancy, drive for muscularity, perceived pressure from and internalisation of appearance ideals, self-esteem, and trait mindfulness. Exploratory factor analyses supported a 1-dimensional factor structure of FAS scores, which was upheld using confirmatory factor analysis. FAS scores were also invariant across sex and there was no significant sex difference in scores. Construct validity was generally supported through significant associations with the additional measures included in the study. Incremental validity was also established insofar as functionality appreciation predicted self-esteem over-and-above the variance accounted for by other body image measures. The availability of the Malay FAS will be of use to scholars in Malaysia, but establishing cross-linguistic invariance will be an important next step.